Ljósvetninga saga / Saga degli abitanti di Ljósavatn - Gavilli, Ruben (Biblioteca di Studi di Filologia Moderna, 2022)
This volume offers the first Italian translation of Ljósvetninga saga, composed in the thirteenth century, belonging to the genre of íslendigasögur, the "sagas of the Icelanders". The volume contextualizes the work in the Medieval Icelandic literature's framework and offers an overlook at philological issues, such as, for example, the relationship between the existing manuscripts and the genesis of the saga. In addition, the volume also provides a literary analysis of the style, characters and text, based on some of the recent academic studies. The Ljósvetninga saga tells the story of the continuous struggles between two families in Northern Iceland for supremacy over the territory: through the extensive references to legal practices, it remains a precious example of medieval Icelandic culture.